2011
DOI: 10.2172/1015523
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fish Passage Conditions through a Francis Turbine and Regulating Outlet at Cougar Dam, Oregon, Using Sensor Fish, 2009?2010

Joanne P. Duncan

Abstract: Fish passage conditions through a Francis turbine and a regulating outlet (RO) at Cougar Dam on the south fork of the McKenzie River in Oregon were evaluated by Pacific Northwest National Laboratory for the U.S. Army Corps of Engineers, Portland District, using Sensor Fish devices. The objective of the study was to describe and compare passage exposure conditions, identifying potential fish injury regions encountered during passage via specific routes. The RO investigation was performed in December 2009 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Monzyk and others (2011) estimated passage survival based on fish with passive integrated transponder (PIT) tags, and reported survival estimates for the RO route similar to those of the balloon-tagged fish and survival estimates for the powerhouse route greater than those of the balloon-tagged fish. Duncan (2011) passed sensor packages through the two routes and found more severe conditions within the powerhouse route than in the RO route, corroborating the results described by Normandeau and Associates, Inc. (2010) and Monzyk and others (2011). In November 2011, Beeman and others (2012) estimated that dam passage single-release survival of radio-tagged subyearling Chinook salmon from entry into the temperature control tower to detection at a site 3 km downstream was 0.3860 for fish passing through the powerhouse and 0.4247 for fish passing through the RO (expressed as probabilities rather than percentages).…”
Section: Weir Gatessupporting
confidence: 87%
See 2 more Smart Citations
“…Monzyk and others (2011) estimated passage survival based on fish with passive integrated transponder (PIT) tags, and reported survival estimates for the RO route similar to those of the balloon-tagged fish and survival estimates for the powerhouse route greater than those of the balloon-tagged fish. Duncan (2011) passed sensor packages through the two routes and found more severe conditions within the powerhouse route than in the RO route, corroborating the results described by Normandeau and Associates, Inc. (2010) and Monzyk and others (2011). In November 2011, Beeman and others (2012) estimated that dam passage single-release survival of radio-tagged subyearling Chinook salmon from entry into the temperature control tower to detection at a site 3 km downstream was 0.3860 for fish passing through the powerhouse and 0.4247 for fish passing through the RO (expressed as probabilities rather than percentages).…”
Section: Weir Gatessupporting
confidence: 87%
“…The differences in the allocation and magnitudes of the discharge led to differences in the RO gate openings between years with an average of 1.21 ft during the day and 3.18 ft at night in 2012 and 1.25 ft (assumed constant during day and night) in 2011. Previous studies have shown survival and passage conditions to improve with RO gate opening size at Cougar Dam (Duncan, 2011;Monzyk and others, 2011). Thus, the greater RO gate opening during the night in November 2012 may be one reason for the higher survival in 2012 compared to 2011.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Fish in the RO study were a mean length of 172 mm (range 127-209 mm), and in the powerhouse study were a mean length of 179 mm (range 124-230 mm; Normandeau Associates, Inc., 2010b). Study conditions included a 1.5-ft RO opening at 440 ft 3 /s and 3.7-ft RO opening at 1,040 ft 3 /s when the reservoir elevation was near winter low pool (1,532-1,541 ft; Normandeau Associates, Inc., 2010b;Duncan, 2011). The turbine evaluation included three separate treatment conditions for unit 2: (1) minimum wicket opening and 340 ft 3 /s, (2) maximum wicket opening and 550 ft 3 /s, and (3) peak efficiency wicket opening and 455 ft 3 /s (Normandeau Associates, Inc., 2010b).…”
Section: Passage Routes and Effects Of Operationsmentioning
confidence: 99%
“…The turbine evaluation included three separate treatment conditions for unit 2: (1) minimum wicket opening and 340 ft 3 /s, (2) maximum wicket opening and 550 ft 3 /s, and (3) peak efficiency wicket opening and 455 ft 3 /s (Normandeau Associates, Inc., 2010b). Duncan (2011) used sensor fish and reported a high incidence of one or more significant strike, collision, or shear events (acceleration magnitude greater than 95 g) in the RO and powerhouse outlets (more than 92 percent). Nearly 86 percent of trials resulted in multiple significant events during passage through the powerhouse and RO.…”
Section: Passage Routes and Effects Of Operationsmentioning
confidence: 99%